2011
DOI: 10.1007/s00395-011-0185-9
|View full text |Cite
|
Sign up to set email alerts
|

Remote intermittent ischemia before coronary artery bypass graft surgery: a strategy to reduce injury and inflammation?

Abstract: Perioperative myocardial ischemia contributes to postoperative morbidity and mortality. Remote intermittent ischemia (RI) has been shown to benefit patients undergoing coronary artery bypass graft (CABG) surgery by decreasing postoperative cardiac troponin levels. In addition, there is evidence that volatile anesthetics may provide myocardial protection. In this prospective randomized controlled trial we tested the hypothesis that RI is cardioprotective under a strict anesthetic regime with volatile anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 39 publications
3
88
0
1
Order By: Relevance
“…Subgroup analysis of the studies reporting outcomes of CABG with or without AVR showed results consistent with the general trend (SMD -0.42; 95% CI: -0.70 to -0.13, p = 0.005) and I 2 = 67% [9,[20][21][22][23][24][25][26][27]. Studies concerning isolated valvular surgery did not confirm the protective result of rIPC; however, heterogeneity (I 2 = 94%) was essentially influencing the outcome effect under the random [28][29][30].…”
Section: Sensitivity Analysissupporting
confidence: 63%
See 4 more Smart Citations
“…Subgroup analysis of the studies reporting outcomes of CABG with or without AVR showed results consistent with the general trend (SMD -0.42; 95% CI: -0.70 to -0.13, p = 0.005) and I 2 = 67% [9,[20][21][22][23][24][25][26][27]. Studies concerning isolated valvular surgery did not confirm the protective result of rIPC; however, heterogeneity (I 2 = 94%) was essentially influencing the outcome effect under the random [28][29][30].…”
Section: Sensitivity Analysissupporting
confidence: 63%
“…Finally, fifteen papers were found to present the best available evidence. These studies pertained to: adult coronary bypass grafting surgery with or without AVR [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], adult valvular surgery [28][29][30], and pediatric cardiac surgery [31][32][33]. All the available papers were designed as prospective randomized controlled trials.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations